2001
DOI: 10.1038/35101621
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled-7 signalling controls tissue separation during Xenopus gastrulation

Abstract: Cell signalling through Frizzled receptors has evolved to considerable complexity within the metazoans. The Frizzled-dependent signalling cascade comprises several branches, whose differential activation depends on specific Wnt ligands, Frizzled receptor isoforms and the cellular context. In Xenopus laevis embryos, the canonical beta-catenin pathway contributes to the establishment of the dorsal-ventral axis. A different branch, referred to as the planar cell polarity pathway, is essential for cell polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
217
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(228 citation statements)
references
References 21 publications
11
217
0
Order By: Relevance
“…Inhibition of canonical Wnt signalling by a dominant-negative form of Tcf3 does not inhibit neural crest migration (F. Romero and R.M., unpublished). There is convincing experimental evidence that shows that canonical Wnt signalling is involved in neural crest induction and cell differentiation (Dorsky et al, 1998;Garcia-Castro et al, 2002;LaBonne and Bronner-Fraser, 1998;Lee et al, 2004 (CarreiraBarbosa et al, 2003;Djiane et al, 2000;Kuhl et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Wang and Malbon, 2004;Winklbauer et al, 2001). We have shown that Fz7 is expressed in the premigratory neural crest just before migration, as well as in the migrating neural crest.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Inhibition of canonical Wnt signalling by a dominant-negative form of Tcf3 does not inhibit neural crest migration (F. Romero and R.M., unpublished). There is convincing experimental evidence that shows that canonical Wnt signalling is involved in neural crest induction and cell differentiation (Dorsky et al, 1998;Garcia-Castro et al, 2002;LaBonne and Bronner-Fraser, 1998;Lee et al, 2004 (CarreiraBarbosa et al, 2003;Djiane et al, 2000;Kuhl et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Wang and Malbon, 2004;Winklbauer et al, 2001). We have shown that Fz7 is expressed in the premigratory neural crest just before migration, as well as in the migrating neural crest.…”
Section: Discussionmentioning
confidence: 86%
“…Although no specific Wnt11 receptor has been identified, there is some evidence that suggests that PCP Wnt signalling involves Fz7 (Carreira-Barbosa et al, 2003;Djiane et al, 2000;Medina et al, 2000;Sumanas and Ekker, 2001;Winklbauer et al, 2001). We examined the distribution of the Fz7 receptor in neural crest cells.…”
Section: Resultsmentioning
confidence: 99%
“…During development, FZD7-mediated tissue movement or cell migration involves non-canonical Wnt signalling. For example, neural crest cell migration in birds is mediated by Wnt11/FZD7 (De Calisto et al, 2005); and tissue separation (Winklbauer et al, 2001) and convergent extension movements (Djiane et al, 2000) during Xenopus gastrulation are via FZD7-mediated noncanonical Wnt/Ca 2 þ and Wnt/PCP pathways, respectively (reviewed in Kuhl, 2002;Tada et al, 2002). In contrast, FZD7-mediated tissue construction or epithelialization involves canonical Wnt signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Frizzled-7 (FZD7) is a seven-pass trans-membrane Wnt receptor that governs developmental morphogenetic events such as gastrulation (Winklbauer et al, 2001;Tada et al, 2002). Gastrulation is a series of coordinated movements of cell groups to establish the basic body plan of vertebrate embryos and as such involves remarkable changes in cell morphology, cell adhesion, cell-cell junction and cell mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Many of FZD receptors, including FZD3 and FZD7, are able to activate the canonical b-catenin pathway, whereas data are not so obvious for FZD6. The noncanonical PKC and JNK pathways have been clearly shown as potentially activated by some FZD family members as FZD7, whereas it remains ambiguous for FZD3 and FZD6 (He et al, 1998;Winklbauer et al, 2001;Kinoshita et al, 2003;Merle et al, 2004;Katoh, 2007;Katoh and Katoh, 2007b). We have previously reported that the FZD7-mediated signalling was able to control the cancerous phenotype of human HCC cell lines through b-catenin protein regulation, and that one of the Wnt ligand candidate activators is WNT3 (Merle et al, 2004(Merle et al, , 2005Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%